Accelerating Stunting Reduction By Porong Community Health Center In Sidoarjo Regency - Fania Khalsa Utami Baroroh; Sri Wibawani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Stunting is a health issue in Indonesia that causes children to suffer from chronic malnutrition, which hinders physical growth and brain development. Children who experience stunting tend to have shorter stature and less than optimal growth and development. The Porong Health Center is one of the health centers innovating by implementing digital services and winning an award through the KOPI PAHIT application. The purpose of this study is to analyze and describe the strategies of the Porong Health Center in Sidoarjo to accelerate the reduction of stunting. In this study, the author applied a qualitative research process with the aim of providing a comprehensive and detailed description of the research study. Data collection was conducted through interviews, observations, documentation, and literature reviews. The findings of this study indicate that the Porong Health Center in Sidoarjo's strategy to reduce stunting has successfully shown a significant decrease, although there are still fluctuations in stunting rates in some villages due to economic factors and food security. The health center has improved maternal and child health services. The innovative KOPI program increased community participation. It successfully raised community awareness through education and guidance. It successfully optimized the data monitoring and evaluation system. It also successfully improved cross-sector collaboration